Nutrient profiles of the hybrid grape cultivar 'Isabel' during berry maturation and ripening. (25th November 2016) - Kurt, Aynur; Torun, Hülya; Colak, Nesrin; Seiler, Gerald; Hayirlioglu‐Ayaz, Sema; Ayaz, Faik Ahmet
Abstract: BACKGROUND: The hybrid grape cultivar 'Isabel' ( Vitis labrusca × V. vinifera ) is widely grown in the Black Sea region of Turkey and constitutes an important part of the diet of its inhabitants. Phenological and ampelographic studies of the grape have previously been performed, but there are no data concerning nutrient composition. Its nutrient content needs to be investigated to ascertain its potential economic and nutritional uses in the region. RESULTS: The concentrations (range, g kg −1 fresh weight) of major soluble sugars (fructose 2.08–79.70; glucose 3.71–66.74) increased and those of organic acids (tartaric acid 0.05–6.60; malic acid 2.38–9.92) decreased in the skin and pulp during ripening. The major fatty acid was linoleic acid in the skin (50.13), pulp (18.11) and seed (704), while the main minerals (dry weight) were potassium (2.70–19.70), followed by phosphorus (0.53–3.40) and calcium (0.42–5.90) in the parts. CONCLUSION: Berry maturation and ripening significantly influenced the concentrations of sugars and organic acids the most in the skin and pulp, but did not significantly affect the concentrations of fatty acids and minerals in the 'Isabel' grape. Our findings also suggest an optimal harvest time in terms of levels of the nutrients. © 2016 Society of Chemical Industry